Trust, Expertise and Public Appeal: Factors Influencing Perceptions of Political Brand Ambassadors in Indonesian Political Marketing - Vita Subiyakti; Mohamad Irhas Effendi; Dyah Sugandini (DINASTI RESEARCH, 2026)
The transformation of government communication in the digital age has led to an increase in the personalization of public policy communication through government officials who serve as political brand ambassadors. In the context of fiscal policy communication, the credibility of the Minister of Finance is a key factor in shaping public attitudes and perceptions toward government policies. This study aims to analyze the influence of trustworthiness, expertise, and attractiveness on attitudes toward the political brand ambassador and its implications for the perception of the political brand ambassador in the figure of the Minister of Finance of the Republic of Indonesia, Purbaya Yudhi Sadewa. The study employs a quantitative approach using a survey method involving 310 respondents and is analyzed using PLS-SEM. The results indicate that trustworthiness and attractiveness have a positive and significant effect on attitudes toward the political brand ambassador, while expertise does not have a significant effect. Furthermore, attitudes toward the political brand ambassador were found to have a positive effect on perceptions of the political brand ambassador and mediate the effects of trustworthiness and attractiveness, but do not mediate the effect of expertise. These findings suggest that public perception of government officials is more influenced by integrity and symbolic appeal than by technocratic competence alone. This study contributes to the development of Source Credibility Theory within the context of political marketing and public policy communication in the digital age.